Studi sebaran sedimen berdasarkan ukuran butir di perairan Kuala Gigieng, Kabupaten Aceh Besar, Provinsi Aceh - Syahrul Purnawan; Ichsan Setiawan; Marwantim M (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The objective of gacorwin the present study was to evaluate the distribution of sediments in the estuary of Kuala Gigieng. The study was done on Mei to June 2011 and the sampling was conducted in three areas of estuary i.e. downestuarine, middle-estuarine and river section of Kuala Gigieng. The wet sieving analysis method was used in this study. The data was then weighed and the percentage was calculated and classified based on the Wentworth scale. The gacorwin results showed that (1) the mean grain size of sediment of each area was 0.50 mm, 0.65 mm and 0.56 mm and gacorwin the characteristically, the sediment distribution was consisted of medium sand 63.42%, fine sand 23.40%, coarse sand 5.59%, very fine sand-mud 4.13% and pebble 0.17%. The currents speed were 0.25 m/s, 0.23 m/s and 0.19 m/s. The current speed has influenced the sediment distribution where small grains were mostly found at higher current speed. Key words. Estuary, currents and sediment distribution